Obesity Management In Adults Among Primary Care Doctors: A Qualitative Study - Zaid Ahmad Khan, Ezzah Dalilah (2023)
Number of people living with obesity are on the rise worldwide. Malaysia, too, is not spared from the global epidemic of obesity and has been labelled as the fattest nation in Southeast Asia. The objectives aimed are (1) to explore the factors influencing obesity management in adults among PCDs, (2) to investigate the experiences and perceptions of PCDs in obesity management in adults, (3) to evaluate the knowledge of obesity management in adults among PCDs, and (4) to determine the enablers and barriers in obesity management in adults among PCDs. This study adopted a qualitative methodology and in-depth interviews (IDIs) guided with semi-structured questionnaire. Ten PCDs were selected purposively to participate in the study. Interviews were conducted virtually where all the audio recordings were transcribed verbatim before being exported to the ATLAS.ti 8 software for data analysis. Thematic analyses were applied to identify common themes when data saturation was achieved. The findings revealed that PCDs have limited knowledge, received minimal training and support in managing obesity among adults. Undoubtedly, primary care is the best setting for patients to seek obesity treatment for its accessibility and continuity of care. Managing obesity would be successful when PCDs are well equipped with knowledge and training, able to sustain patients’ motivation, and receive sufficient support from the healthcare system.